2020
DOI: 10.1002/er.5903
|View full text |Cite
|
Sign up to set email alerts
|

Experimental and simulation approach of the loop geometry effect on the natural circulation system of the advanced nuclear reactor

Abstract: Summary Lately, natural circulation has become an exciting topic because it has been proposed and applied in some advanced nuclear reactors as a passive safety system. The aim of the present study is to examine the effect of the loop geometry on the natural circulation based cooling system of a given power source. The experimental approach was achieved by the construction of two natural circulation loops with vertical heater and vertical cooler. Both circulation loops were built with a same vertical length of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…Then, the authors' work has been done on paper [9], demonstrated experimentally that expansion tank placement is crucial in single-phase NCLs. Also, subsequent work by experimental and modelling showed that loop geometry could affect natural circulation-based cooling systems [9][10][11][12]. These studies revealed that the instability of the NCL is influenced by the loop geometry.…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…Then, the authors' work has been done on paper [9], demonstrated experimentally that expansion tank placement is crucial in single-phase NCLs. Also, subsequent work by experimental and modelling showed that loop geometry could affect natural circulation-based cooling systems [9][10][11][12]. These studies revealed that the instability of the NCL is influenced by the loop geometry.…”
Section: Introductionmentioning
confidence: 95%
“…The effect of coolant temperature variations on NCL instability was analysed in paper [19] using the commercial code Fluent 6.3. Also, the authors have modelled the effect of the natural circulation loop geometry using the COMSOL Multiphysics software [10,11]. Motivated from the above description, in this paper, we studied the transient and steady-state of the natural circulation system in the molten salt loop with vertical heater and horizontal cooler using computational fluid dynamics.…”
Section: Introductionmentioning
confidence: 99%
“…The study showed that in a certain condition, the mass flow rate due to buoyancy force will be chaotic. A two-dimensional numerical model for the NC loop and its validation was developed by Hariyanto et al [12]. The model represents the mass flow rate of various geometrical and flow rate variations of the system.…”
Section: Introductionmentioning
confidence: 99%